2017
DOI: 10.1051/0004-6361/201628936
|View full text |Cite
|
Sign up to set email alerts
|

Barlenses and X-shaped features compared: two manifestations of boxy/peanut bulges

Abstract: Context. Morphological characteristics of Boxy/Peanut bulges are studied, in particular whether most of the flux associated to bulges in galaxies with masses similar to those of the Milky Way at redshift z∼0, could belong to vertically thick inner part of the bar, in a similar manner as in the Milky Way itself. At high galaxy inclinations such structures manifest as Boxy/Peanut/X-shape features, and near to face-on view as barlenses. We also study the possibility that bulges in some fraction of unbarred galaxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 106 publications
(127 reference statements)
4
40
0
1
Order By: Relevance
“…Erwin & Debattista 2013, Fragkoudi et al 2015, Ciambur & Graham 2016, Savchenko et al 2017). The method followed in this paper is based on Laurikainen & Salo (2017). The tips of the X-shape branches are determined visually on the unsharp-masked images, and these measurements were repeated three times for different window sizes.…”
Section: B/p Identification and Size Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Erwin & Debattista 2013, Fragkoudi et al 2015, Ciambur & Graham 2016, Savchenko et al 2017). The method followed in this paper is based on Laurikainen & Salo (2017). The tips of the X-shape branches are determined visually on the unsharp-masked images, and these measurements were repeated three times for different window sizes.…”
Section: B/p Identification and Size Measurementmentioning
confidence: 99%
“…Figure 11. B/P box size measurements compared with the ones obtained by Laurikainen & Salo (2017) of edge-on galaxies from S 4 G and NIRS0S. Starred points indicates bars in buckling, and only the longest semi-minor axis b X is considered in these cases.…”
Section: Discsmentioning
confidence: 99%
See 1 more Smart Citation
“…They proposed that this particular structure of large boxy bulges can be a result of accreted material of merging satellites or can be barlenses (see e.g. Laurikainen & Salo 2017;Laurikainen et al 2018). Similarly, the existence of galaxy stellar halos is naturally explained as a by-product of hierarchical galaxy formation by the accretion and disruption of infalling satellites (see Ann & Park 2018, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…2. Laurikainen & Salo (2017) have recently shown that with a concentrated bulge component, an in-plane bar obtains a barlens morphology. Such a barlens is small, typically 0.5 or less than a bar major axis.…”
Section: Discussionmentioning
confidence: 99%